2019
DOI: 10.1038/s41598-019-41334-7
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty in hydrological analysis of climate change: multi-parameter vs. multi-GCM ensemble predictions

Abstract: The quantification of uncertainty in the ensemble-based predictions of climate change and the corresponding hydrological impact is necessary for the development of robust climate adaptation plans. Although the equifinality of hydrological modeling has been discussed for a long time, its influence on the hydrological analysis of climate change has not been studied enough to provide a definite idea about the relative contributions of uncertainty contained in both multiple general circulation models (GCMs) and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
99
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(115 citation statements)
references
References 101 publications
(104 reference statements)
3
99
1
Order By: Relevance
“…If that was indeed true, then it would be justifiable to use any uncalibrated hydrological model to project future hydrological fluxes and state variables. However, a recent study demonstrated that while uncertainty of GCM projections was the dominant source for faster components of hydrologic response like surface runoff, the uncertainty of hydrological model parameterization was found to be a significant source of uncertainty, particularly for slow response components (Her et al, 2019). This finding indicates that calibration of hydrological models is still important…”
Section: Interactive Commentmentioning
confidence: 99%
“…If that was indeed true, then it would be justifiable to use any uncalibrated hydrological model to project future hydrological fluxes and state variables. However, a recent study demonstrated that while uncertainty of GCM projections was the dominant source for faster components of hydrologic response like surface runoff, the uncertainty of hydrological model parameterization was found to be a significant source of uncertainty, particularly for slow response components (Her et al, 2019). This finding indicates that calibration of hydrological models is still important…”
Section: Interactive Commentmentioning
confidence: 99%
“…However, applying hydrological models in the real world is often challenged by calibration, validation, and predictability issues [7][8][9][10]. During the calibrated process, parameter sensitivity and uncertainty analysis often become a hurdle, even though hydrological models are normally calibrated to find optimal parameters set with the optimum objective functions [11][12][13]. Unless there is a careful sensitivity and uncertainty analysis, overestimation or underestimation of hydrologic regimes can cause over-design of mitigation measures or insufficient preparation for potential situation [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been many studies involving sensitivity analysis, uncertainty fitting and performance evaluation of SWAT model all over the world [2,11,14,16,18,35], identifying dominant parameters, reducing the magnitude of uncertainties for streamflow simulation and confirming actual hydrological processes still remain essential for some distinct regions. Uncertainties in hydrological modeling come from input data, model structure, and parameters [2,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…New hydrological datasets from earth observations, hydrological and land-surface models, as well as seasonal forecasts continue to be developed and tested around the world. The quality of these datasets has been improving rapidly due to the consideration of longer periods of record, increasingly finer spatial resolutions, better accuracy in hydrological estimates and predictions, and the consideration of uncertainty through ensembles (Derin et al, 2016;Dijk et al, 2016;Her et al, 2019;Orth et al, 2017;Schellekens et al, 2017). For example, a new version of MSWEP global precipitation dataset (historic dataset over 30 years) was enhanced from a 0.25 degree to a 0.1 degree spatial resolution in less than one year (Beck et al, 2017b(Beck et al, , 2018.…”
Section: Synthesismentioning
confidence: 99%